What explains the variation in dam impacts on riverine macroinvertebrates? A global quantitative synthesis. (3rd December 2020) - Wang, Jun; Ding, Chengzhi; Heino, Jani; Jiang, Xiaoming; Tao, Juan; Ding, Liuyong; Su, Wan; Huang, Minrui; He, Daming
Abstract: Dams have fragmented rivers and threatened aquatic biodiversity globally. However, the findings regarding dam impacts on riverine macroinvertebrates vary across regions and taxa. We conducted a global meta-analysis to quantify the effects of dams on macroinvertebrate assemblages (i.e. species richness and abundance) based on 3849 data points extracted from 54 publications. Responses of macroinvertebrates to dams varied among climatic zones, dam altitudes, dam sizes (i.e. height), downstream distances from the dams, and taxonomic groups. The overall effect size of dams on macroinvertebrate richness was negative, while that of dams on abundance was positive but varied among different dam types. Richness reductions were most pronounced in cold regions and high-altitude regions and were least pronounced in tropical regions and low-altitude regions, while abundance increases were more obvious in tropical regions and low-altitude regions. Macroinvertebrate richness reduction and abundance increase were coupled (i.e. when the richness slightly decreased, the increase in abundance was more significant, and vice versa) under the influence of dams across different climatic zones, altitudes, dam heights, and downstream distances from the dams. Furthermore, different taxonomic groups responded variably to dams, with stoneflies (Plecoptera), caddisflies (Trichoptera) and true bugs (Hemiptera) being the most sensitive groups (i.e. significant reduction in richness) among the taxa examined. Macroinvertebrate richness reductions were primarily attributed to changes in downstream substrate composition (i.e. from coarse to fine substrates), while abundance increases were potentially caused by replacements among taxa at downstream sites. Collectively, our results contribute to improving the prediction of the effects of dams on riverine macroinvertebrate assemblages and are valuable for guiding assessment and monitoring of river ecosystems, as well as sustainable dam development, planning and restoration.